Effects of plant growth – promoting rhizobacteria and nitrogen on growth of pegaga (Centella asiatica (L.)) in a hydroponic system - Syed Ja'afar, Syed Nazeri Shah Putra (2015)
Centella asiatica (L.), pegaga, is a small creeping herb. It is one of the top 5 Malaysian herbs categorized for their medicinal quality to enhance the national income. C. asiatica is known to aid in the treatments of wounds, ulcers, skin diseases, tuberculosis and various mental disorders. Plant Growth-Promoting Rhizobacteria (PGPR) are defined as root colonizing bacteria which increase plant nutrient uptake and promote plant growth and development. This experiment was carried out to study the effects of different PGPR and nitrogen levels on growth of C. asiatica under hydroponic system. The objective of this experiment was to determine the best PGPR strain and the optimum level of nitrogen for increased vegetative growth of C. asiatica under hydroponic system. The three selected PGPR strains (UPMB10, Rhizospheric and Endophytic pegaga isolates)were inoculated toC. asiatica with three different levels of nitrogen (0%, 33% and 100%)in test tubes and left for 21 days in a plant growth chamber with twelve treatments and three replications using a Completely Randomized Design (CRD).The parameters were incremental height and leaf greenness (SPAD values). The data were analyzed using ANOVA and the means were compared by using Tukey test. At the end of the experiment, it was observed that there was no significant difference between all treatments for incremental height (growth rate) at week 1 and week 3 and leaf greenness (SPAD values). However, a significant difference was observed in incremental height (growth rate) between N levels at week 2. The best PGPR strain that have a good relationship with the optimum usage of nitrogen for C.asiatica were U strain (UPMB- 10) and E strain (endophytic) with 0 % nitrogen, which had higher incremental heights and greenness of leaves compared to R strain.